Language learning experience of two Vietnamese language adult learners - Cao Thi Hong Phuong (EduLite: Journal of English Education, Literature and Culture, 2018)
In-depth research on Second Language Acquisition (SLA) has shed light on different factors affecting learners’ process of learning an additional language (AL). The well-researched factors may include age, inter-linguistic influences, language aptitude, cognition, motivation, and so forth. This case study report compares two adult learners’ language learning experiences from social and cognitive SLA perspectives. The key findings reveal that both of the learners mostly relied on three significant factors such as motivation, learners’ identity and inter-linguistic influences to acquire the language. From the findings, the paper then suggests some pedagogical implications to maximize the effectiveness of English classroom practices.